Species Composition of Amphibians (Order Anura) in Baturraden Botanical Garden, Banyumas - Erik Prasetyo (International Journal of Applied Biology, 2020)
Baturraden botanical garden is located in Kemutuk Lor village, Baturraden district, Banyumas in the southern slopes of Mount Slamet. This area is mostly composed by the forest cover (natural forests and production forests) and has a high water abundance so in accordance with the habitat of amphibians (order Anura). This study aims to determine the species composition of amphibians (order Anura) in the area of the Baturraden botanical garden. This research was conducted in July 2015 using the Visual Encounter Survey (VES) method by making three line transects. Results of the study found 8 species of amphibians (order Anura) from 5 families that were families from Megrophryidae (Leptobrachium haseltii), Bufonidae (Leptophryne borbonica), Dicroglossidae (Limnonectes kuhlii), and (Limnonectes microdiscus), Ranidae (Hylarana chalconota and Odorrana hosii) and Rhacophoridae (Polypedates leucomystax and Rhacophorus margaritifer). Family composition is dominated from family Dicroglossidae and Ranidae.